Pengaruh Reward and Punishment dan Persepsi Dukungan Organisasi terhadap Produktivitas Karyawan Rumah Makan Kasum Cilacap - Pungki Wahyu Diana; Allya Roosallyn Assyofa; Fajar Alamsyah, Indra (Bandung Conference Series: Business and Management, 2024)
Abstract. In the process, the business world must pay attention to the importance of human resource management (HR) for productivity. Of course, HR management must pay attention to the fairness provided by the company or organization and the facilities provided to its employees. The relationship between justice and the facilities provided for employee productivity is closely related to the theory of HR Management. This research has three main objectives, namely to partially determine the influence of reward and punishment on employee productivity, the impact of perceived organizational support on productivity partially, and the influence of reward and punishment, and perceived organizational support on productivity simultaneously. Kasum Cilacap Restaurant was used as the object of this research, and as many as 40 employees were used as subjects in this research which were then processed statistically with the help of the IBM SPSS Version 26.0 application. This research uses a regression test to find partial effects and an F test to find simultaneous effects. The results of this research indicate that there is a simultaneous influence of reward and punishment on employee productivity and perceptions of organizational support for employees. In addition, it was found that there was a partial influence on reward and punishment, and perceptions of organizational support on employee productivity. Abstrak. Dunia bisnis dalam prosesnya haruslah memperhatikan pentingnya manajemen sumber daya manusia (SDM) untuk produktivitasnya. Tentunya dalam manajemen SDM harus memperhatikan keadilan yang diberikan oleh perusahaan atau organisasi, dan fasilitas apa yang diberikan kepada karyawannya. Keterkaitan antara keadilan dan fasilitas yang diberikan terhadap produktivitas karyawan sangat terkait dengan teori Manajemen Sumber Daya Manusia. Penelitian ini memiliki tiga tujuan utama yaitu mengetahui pengaruh reward and punishment terhadap produktivitas karyawan secara parsial, pengaruh persepsi dukungan organisasi terhadap produktivitas secara parsial, dan pengaruh reward and punishment, dan persepsi dukungan organisasi terhadap produktivitas secara simultan. Rumah Makan Kasum Cilacap dijadikan objek dalam penelitian ini, dan sebanyak 40 karyawan dijadikan sebagai subjek dalam penelitian ini yang kemudian diolah secara statistik dengan bantuan applikasi IBM SPSS Versi 26.0. Penelitian ini menggunakan uji regresi dalam mencari pengaruh secara parsial dan uji F dalam mencari pengaruh secara simultan. Hasil penelitian ini menunjukkan bahwa adanya pengaruh secara simultan pada reward and punishment terhadap produktivitas karyawan, dan persepsi dukungan organisasi terhadap karyawan. Selain itu, ditemui bahwa terdapat pengaruh secara parsial pada reward and punishment, dan persepsi dukungan organisasi terhadap produktivitas karyawan.